The Impact of Government Subsidies on Electric Vehicle Sales: A Regression analysis of BYD in China - Shan Jierui (SHS Web of Conferences)
This study aims to investigate the impact of Chinese government subsidies on BYD’s electric vehicle sales. Since 2009, the Chinese government has continued to subsidize electric vehicle companies in order to promote low-carbon emissions and boost consumption. As a leading company in China’s new energy vehicle industry, BYD received a total of US$3.7 billion in direct government subsidies between 2018 and 2022, including US$2.2 billion in a single year in 2022. Through a regression analysis model, this study examines the relationship between Chinese government subsidies and BYD’s EV sales. The results show that there is a strong positive correlation between government subsidies and BYD’s EV sales, with increased subsidies significantly driving sales growth. Although BYD achieved partial growth without subsidies, the absence of subsidies may negatively affect the sustained sales growth. This study reveals the importance of government subsidies in driving EV market expansion and provides a strong basis for future policy formulation.